Змова у структурі співучасті у злочині - Кваша, О.; Резнік, Я.; Kvasha, O.; Reznik, Ya. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті обґрунтовано, що змова – це іманентна властивість та структурний елемент співучасті. Структура співучасті у злочині – це система рольових, функціональних і суб’єктивних зв’язків між співучасниками, які вступили у змову і взаємодіють з метою досягнення єдиного злочинного результату й реалізації власних цілей у межах групових. Змова може бути попередньою, коли відбувається між співучасниками до початку виконання об’єктивної сторони злочину. Інший вид змови, не попередню, запропоновано умовно називати ситуативною. Ситуативна змова при співучасті має місце, коли діяльність одного виконавця приєднується до діяльності іншого (інших) виконавця вже в процесі вчинення злочину, але до його закінчення. The article substantiates that a conspiracy is an inherent property and a structural element of complicity. A conspiracy can be a preliminary one, when it occurs between accomplices before the execution of the objective part of the crime.It is proposed to call another, not preliminary kind of conspiracy, a situational one. A situational conspiracy of complicity occurs when one performer’s acts are united with the activity of another participant in the very process of committing the crime, but before its termination. Joint action is the most important sign of complicity which embodies its essence, in fact, distinguishes this form of committing a crime among others. Consequently, in all legislative systems, where the term «conspiracy» is used, it refers to joint actions, the combination of the efforts of at least two persons to achieve a common criminal purpose. The key findings of the study contribute to clarification of the notion of the structure of complicity in a crime. The authors suggest to intpret the structure of complicity in a crime as a system of role, functional and subjective relationships between accomplices who have entered into a conspiracy and interact with a view of achieving a single criminal result and realization of their own goals within the group.
Conspiracy as a Structural Component of Complicity in the Crime
Keywords: змова; співучасть; структура співучасті; попередня змова; ситуативна змова; conspiracy; complicity; structure of complicity; preliminary conspiracy; situational conspiracy